Longitudinal changes of motor cortex function during motor recovery after stroke. Issue 4 (19th May 2023) - Chunyong, Li; Yingkai, Li; Fuda, Liu; Jiang, Che; Liu, Yan
ABSTRACT: Background and purpose: Functional magnetic resonance imaging (fMRI) combined with behavioral assessments was used in our study to investigate the dynamic process of motor cortical functional reorganization after infarction. Therefore, we could provide a theoretical basis and build a useful evaluation system for rehabilitation after stroke and various other cerebral injuries. Methods: Acute stroke patients with a single lesion in the middle cerebral artery supply area and age- and sex-matched healthy volunteers were recruited. A longitudinal observational study involving 20 patients with stroke was conducted using repeated fMRI. Task-based fMRI data were acquired 3 times over a period of 3 months. The behavioral assessment included dynamometer and finger-tapping tests to evaluate the strength and dexterity of each upper arm. Results: Behavioral results: The behavioral assessments demonstrated large improvements in session 2 and session 3. fMRI results: The healthy group showed activation in the contralateral primary sensory-motor cortex (S1M1) when executing tasks with either the left or right hand. Compared with the healthy subjects, the patients demonstrated greater activation in the ipsilateral frontal and parietal cortices and supplementary motor areas (SMAs). Across all sessions, more motor activation was observed in the left infarction group. Conclusions: Our results show that motor cortical activation induced by moving the paretic hand changes over time. There were differences in motor functional recovery and motor cortex compensation between the dominant hemisphere and nondominant hemisphere after stroke.